Data Visualization Analysis of Bajolbae Application Users Using Tableau - Paris Olivia (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2025)
The Bajolbae application was developed to facilitate small traders and the general public in fulfilling their basic food needs online without requiring face-to-face interaction. The primary issue identified is the absence of a comprehensive analysis of user characteristics, including the level of application utilization based on demographic factors. This study aims to analyze user patterns of the Bajolbae application through data visualization using Tableau based on age, gender, and residential district. The research data were obtained from Pasar DHD (Darsa Hakam Darussalam) as the manager of the Bajolbae application and were processed using Tableau visualization techniques to produce informative graphical representations. The results indicate that adults constitute the dominant age group of users, women represent the largest group of users, and Sako District has the highest number of users. These findings are expected to assist the company in formulating strategies to increase the number of users and to support the development of application features.